On self-sustained detonation. Issue 1 (1st January 2019) - Liu, Weiming
Abstract: Steady and self-sustained detonation is a fundamental element for combustion theory. There is already a theory on it, however, author of this work found that the theory is not perfect and it is necessary to develop new theory, which is the objective of this work. To that end, author firstly discusses the deficiencies of the existing theory. Then, based on the work [1], author introduced a new theoretic model for the self-sustained detonation, an eigenvalue problem. The new model removes the deficiencies in the existing theory and can produce all the information of the detonation, including its speed and structure. This paper focuses on the theoretic analysis on the new concept and is the first part of the work. A direct numerical simulation (DNS) for the self-sustained detonation was carried out as well. Comparison of the results of the DNS, the new theoretic model and the existing theory shows that the introduced new model produced the results identical with the DNS results but significantly different from the results done by the existing theory. This is the second part of the work.